Urban green: Integrating ecosystem extent and condition as a basis for ecosystem accounts: examples from the Oslo region - Per Arild Garnåsjordet; Margrete Steinnes; Zofie Cimburova; Megan Nowell; David N. Barton; Iulie Aslaksen (Statistics Norway, Research Department, 2020)
The article enhances the knowledge base for assessment of urban ecosystem services, within UN System of Environmental-Economic Accounting Experimental Ecosystem Accounting (SEEA EEA), which is based on spatial extent accounts (area of ecosystems) and biophysical condition accounts (ecological state of ecosystems). Case studies from the Oslo region are explored, combining land use/land cover maps from Statistics Norway with satellite data. The approach suggests that especially in an urban context, extent and condition accounts are not separate approaches as suggested by SEEA EEA but should be integrated for ecosystem accounting. Moreover, the basic spatial unit should not be fixed, as suggested by SEEA EEA, but should reflect that modelling of different ecosystem services, as basis for trade-offs in urban planning, requires different spatial units to capture urban green elements.
Keywords: Q34; Q56; Q57; Q58; 330; Experimental ecosystem accounting; ecosystem services; urban ecosystems; spatial analysis; land use maps; land cover maps